Advances in electrospun nanofibers for triboelectric nanogenerators. (15th December 2022) - Li, Yi; Xiao, Song; Luo, Yi; Tian, Shuangshuang; Tang, Ju; Zhang, Xiaoxing; Xiong, Jiaqing
Abstract: Electrospun nanofiber demonstrates advantages in permeability, surface wettability, mechanical figurability and function integrability, capable of catering to the multi-scenario application requirements of triboelectric nanogenerators (TENG) for distributed energy management, especially significant for energy harvesting and self-powered sensing in wearables and bio-interface electronics. In this article, we systematically reviewed the latest progress of electrospun nanofiber based triboelectric active layer and functional conductors in terms of working mechanism, fabrication strategies, geometrics tunability, function integrations, and performance enhancement mechanism, as well as the corresponding nanofiber TENG device advantages in stretchability, permeability, wettability, attachability, sterilization and degradability. Further, some representative applications of nanofiber TENG in energy harvesting, self-powered sensing, and interactive interfacing were summarized to highlight the superiorities of electrospun nanofiber. Accordingly, the existing challenges and promising solutions for future nanofiber TENG were proposed and highlighted, presenting a roadmap to hopefully steer the development of nanofibers for self-powered interface applications. Graphical Abstract: ga1 Highlights: Electrospun nanofiber provided advanced triboelectric active layer and conductor. Tailorable development of nanofibers is summarized in mechanism and special properties. Electrospun nanofiber brings multi-scenario application of TENGs. Future perspectives for electrospun nanofiber based TENGs are proposed.